Behavior of floating stone columns reinforced with geogrid encasement in model tests - Gu, Meixiang; Mo, Haizhao; Qiu, Jianlin; Yuan, Jie; Xia, Quan (Frontiers in Materials, 2022)
The bearing capacity and deformation characteristics of floating stone columns were complicated and are not thoroughly understood. In the present study, a series of experimental model tests of floating stone columns under vertical plate loading was performed. This study investigated the influence of geogrid encasement on the behavior of floating stone columns and provided valuable insight into the load-displacement behavior, bulging deformation, load transfer mechanism, and the radial stress of the geogrid encasement. The test results show that the bearing capacity of the floating stone column was significantly improved due to the geogrid encasement. The column with longer encasement showed higher stiffness at large settlements. The bulging deformation pattern of the column changed with different encasement lengths. More vertical pressure transferred from the top of the column to the bottom of the column due to the existence of the geogrid encasement. The fully encased stone columns developed high radial stress and achieved effective confinement of the column. The bearing capacities of the floating-encased stone columns with different encasement lengths were controlled by bulging deformation instead of penetration failure, which gave confidence that the floating-encased stone columns were an effective method for field construction in extensive soft soils.